A COMPARISON OF TRUMP AND BIDEN’S POLICIES ON HUMAN RIGHTS ISSUES IN XINJIANG FROM AN IDEOSYNCRATIC PERSPECTIVE - Rusniyanti, Rusniyanti; Sahide, Ahmad (JWP (Jurnal Wacana Politik), 2026)
Studies on the United States’ response to human rights violations in Xinjiang have tended to emphasize structural factors, such as great power rivalry, international norms, and foreign policy instruments, while the role of presidential leadership as an analytical variable has been relatively neglected. This study aims to fill this gap by conducting a comparative analysis of the United States’ foreign policy toward human rights violations in Xinjiang during the Donald Trump and Joe Biden administrations using an idiosyncratic approach. This approach places the leader’s personality, ideological orientation, and policy context as key factors in the foreign policy decision-making process. Research data was collected through a literature review of scientific journals, books, official reports, presidential speeches, and US foreign policy documents from 2017 to 2024. The results show that policies during the Trump era were unilateral and confrontational, marked by the imposition of economic sanctions and harsh rhetoric against China. In contrast, the Biden administration adopted a multilateral and diplomatic approach, emphasizing international cooperation and coordination with allies. These findings confirm that differences in leadership character significantly influence the direction and instruments of U.S. foreign policy, even within the same strategic competition context.